2014
DOI: 10.1371/journal.pone.0099960
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Tolerance and High Degradation Capacity of the Herbicide Mesotrione by Escherichia coli Strain DH5-α

Abstract: The intensive use of agrochemicals has played an important role in increasing agricultural production. One of the impacts of agrochemical use has been changes in population structure of soil microbiota. The aim of this work was to analyze the adaptive strategies that bacteria use to overcome oxidative stress caused by mesotrione, which inhibits 4-hydroxyphenylpyruvate dioxygenase. We also examined antioxidative stress systems, saturation changes of lipid membranes, and the capacity of bacteria to degrade mesot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 66 publications
0
30
0
Order By: Relevance
“…In Bacillus, UDP-glucose has a central role as a metabolite for the synthesis of cell wall envelope polymers (Lazarevic et al, 2005;Grundling and Schneewind, 2007). However, when exposed to mesotrione, the a-phosphoglucomutase is under-expressed (PgcA; Table 1; spot 31), suggesting that the strain Mes11 has an altered membrane glycolipid synthesis as recently observed for Escherichia coli DH5a strain exposed to mesotrione (Olchanheski et al, 2014).…”
Section: 2mentioning
confidence: 64%
See 2 more Smart Citations
“…In Bacillus, UDP-glucose has a central role as a metabolite for the synthesis of cell wall envelope polymers (Lazarevic et al, 2005;Grundling and Schneewind, 2007). However, when exposed to mesotrione, the a-phosphoglucomutase is under-expressed (PgcA; Table 1; spot 31), suggesting that the strain Mes11 has an altered membrane glycolipid synthesis as recently observed for Escherichia coli DH5a strain exposed to mesotrione (Olchanheski et al, 2014).…”
Section: 2mentioning
confidence: 64%
“…Mesotrione, chemically derived from a natural phytotoxin produced by the bottlebrush plant Callistemon citrinus (Mitchell et al, 2001), was developed to minimize adverse effects on the environment. Since mesotrione was marketed in 2003, few microorganisms have been reported to catabolize it (Durand et al, 2006;Batisson et al, 2009;Pileggi et al, 2012;Olchanheski et al, 2014). The detailed biodegradative pathway of mesotrione was only established with some of these microorganisms (Durand et al, 2010;Pileggi et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Escherichia coli DH5‐α can withstand high doses of mesotrione (0.4 mM, corresponding to 10× field rate), and completely degrade the herbicide within 3 h of exposure . From the point of view of this study, and considering that E. coli DH5‐α is not an environmental bacterium, the defense system observed in this strain could be considered as non‐specific knowing that it had no previous contact with mesotrione.…”
Section: Fate Of Mesotrione In the Environmentmentioning
confidence: 96%
“…A toxicity study of sulcotrione (90) showed up-regulation of the genes inducing ROS and antioxidant enzymes in the fava bean cells (Vicia faba), followed by increased lipid peroxidation. Some pathogens, in turn, such as E. coli DH5-α (91) and Pantoea ananatis (92), showed resistance to oxidative stress caused by mesotrione, while human liver cancer Hepg2 cells were only mildly affected by tembotrione (93).…”
Section: -Hydroxyphenylpyruvate Dioxygenase Inhibitorsmentioning
confidence: 99%